2015
DOI: 10.14798/73.2.824
|View full text |Cite
|
Sign up to set email alerts
|

FIRST RECORD OF THREE-SPINED STICKLEBACK (Gasterosteus aculeatus Linnaeus, 1758) IN THE DANUBE BASIN OF CROATIA

Abstract: One specimen of three-spined stickleback (Gasterosteus aculeatus) was found in a puddle near the Mura River in October 2014 near the town of Mursko Središće. This is the first record of this species in the Danube Basin of Croatia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Other documents noted that the stickleback was absent from the upper Danube system until the late 19th century (von Siebold, 1863;Münzing, 1963;Ahnelt, 1986) and most authors agree that the only natural population in Switzerland north of the Alps resided near Basel (Figure 3; Schinz, 1837;Wittmack, 1875;Leuthner, 1877;Fehling et al, 1881;Schulze, 1892;Rauther, 1926;Scheffelt, 1926;Muckle, 1972;Ahnelt, 1986;Ahnelt and Amann, 1994;Ahnelt et al, 1998;Paepke, 2002;Altman et al, 2013), that also served as a popular source location of stickleback for aquarium fish traders in Switzerland (Steinmann, 1936). This historical record implies that stickleback were present in the Lake Constance basin before they established in the upper Danube (Vogt and Hofer, 1909;Gaschott, 1941;Berinkey, 1960;Balon, 1967;Ahnelt, 1986;Cakić et al, 2000;Holcik, 2003;Polačik et al, 2008;Lisjak et al, 2015), making a natural colonization from the Danube unlikely.…”
Section: Origins Of the Threespine Stickleback In Lake Constancementioning
confidence: 99%
“…Other documents noted that the stickleback was absent from the upper Danube system until the late 19th century (von Siebold, 1863;Münzing, 1963;Ahnelt, 1986) and most authors agree that the only natural population in Switzerland north of the Alps resided near Basel (Figure 3; Schinz, 1837;Wittmack, 1875;Leuthner, 1877;Fehling et al, 1881;Schulze, 1892;Rauther, 1926;Scheffelt, 1926;Muckle, 1972;Ahnelt, 1986;Ahnelt and Amann, 1994;Ahnelt et al, 1998;Paepke, 2002;Altman et al, 2013), that also served as a popular source location of stickleback for aquarium fish traders in Switzerland (Steinmann, 1936). This historical record implies that stickleback were present in the Lake Constance basin before they established in the upper Danube (Vogt and Hofer, 1909;Gaschott, 1941;Berinkey, 1960;Balon, 1967;Ahnelt, 1986;Cakić et al, 2000;Holcik, 2003;Polačik et al, 2008;Lisjak et al, 2015), making a natural colonization from the Danube unlikely.…”
Section: Origins Of the Threespine Stickleback In Lake Constancementioning
confidence: 99%
“…The first record of the three-spined stickleback in Serbia was in the Danube River at rkm 92 in 1995 (Cakić, Lenhardt, & Petrović, 2000), although there are unverified earlier records (Lenhardt et al, 2011). The species is present in the Mura River (Upper Danube) in Slovenia (Povž et al, 2015) and was recently recorded in the Croatian part of the Mura due to downstream spreading following a flood event (Lisjak et al, 2015).…”
Section: Western Europementioning
confidence: 99%
“…);Mrakovčić et al (2000a);Mikavica et al (2001);Paepke (2002);Mrakovčić et al (2006);Kottelat and Freyhof (2007);Cano et al (2008);Mäkinen and Merilä (2008);Muhamedagić et al (2008);Sevcsik and Erös (2008);Zanella (2009);Zanella et al (2009a);Lipej and Dulčić (2010);Csipkés et al (2012);DeFaveri et al (2012);Glamuzina et al (2013);Landeka et al (2015);Lisjak et al (2015);Zanella et al (2015);Piria et al (2016b);;Piria et al (2018) Remarks: non-native in Danube River drainage; though some report the existence of two species in Croatia, G. aculetus and G. gymnurus, recent genetic analyses have indicated that this is the species G. aculeatusAnonymous (1896a): Hunting and fishing revenues. Lovačko-ribarski viestnik, 5, 59.…”
mentioning
confidence: 99%